Important genes affecting fibre production in animals: A review - AMBREEN HAMADANI; NAZIR A GANAI; MUBASHIR ALI RATHER; IMRAN BASHIR (Indian Journal of Animal Sciences, 2023)
The realignment of the production profile to respond to demanding market signals is one of the most important challenges that an animal breeders face today. Animal fibre being a significant contributor to the agricultural economy needs special attention. This is especially true for sheep and goats where fibre production can account for as much as 20% of the total gross income. It is therefore necessary to gain a better insight into the genes governing wool traits. Gene mapping studies have identified some chromosomal regions influencing fibre quality and production. These may help in the selection of animals producing better quality wool. These are more efficient and accurate than the conventional techniques. This paper critically reviews various genes governing fibre growth in animals and their importance. Fibre quality and production genes may provide novel insights into our understanding of the science of genetics and breeding. The discovery of new fibre-related genes and their functions may also help in future studies related to fibre development and in the development of new and advanced techniques for the improvement of fibre production and quality.